2018
DOI: 10.1038/s41598-018-30820-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of Twist 1 is protective against insulin resistance of adipocytes and involves mitochondrial dysfunction

Abstract: Insulin resistance (IR) has become a global epidemic that represents a serious hazard to public health. However, the precise mechanisms modulating IR have not been fully elucidated. The present study aimed to investigate the role of transcriptional factor Twist 1 in adipocyte IR and to further explore the molecular mechanism. An in vitro IR model based on cultured 3T3-L1 adipocytes was established under high glucose/insulin stimulation and an in vivo IR model in C57/BL6J mice induced by a high fat diet (HFD) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…Total protein was extracted using radioimmunoprecipitation assay (RIPA) lysis buffer containing protease inhibitor cocktail (Thermo Scientific, USA) and phosphatase inhibitor cocktail (Thermo Scientific, USA), and the protein concentration was analyzed by Pierce™ BCA protein assay as previously shown [ 14 , 15 ]. The protein (40 μg for each sample) was resolved on SDS-PAGE gels and transferred to a Hybond-P PVDF membrane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total protein was extracted using radioimmunoprecipitation assay (RIPA) lysis buffer containing protease inhibitor cocktail (Thermo Scientific, USA) and phosphatase inhibitor cocktail (Thermo Scientific, USA), and the protein concentration was analyzed by Pierce™ BCA protein assay as previously shown [ 14 , 15 ]. The protein (40 μg for each sample) was resolved on SDS-PAGE gels and transferred to a Hybond-P PVDF membrane.…”
Section: Methodsmentioning
confidence: 99%
“…The authors’ research team has previously reported that two transcription factors, TWIST1 and PPARγ, have a positive regulatory role in the insulin sensitivity of 3 T3-L1 adipocytes [ 14 ]. In IR models of 3 T3-L1 adipocytes and C57/BL6J mice, silencing TWIST1 expression can relieve IR to a certain degree, indicating the potential clinical value of TWIST1 and PPARγ in steatosis-related disease [ 15 ]. As hepatocytes are target cells of insulin, the role of TWIST1 and PPARγ in hepatocytes is undoubtedly worth further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Heterozygous knockout mice of Twist1 showed an obesity-resistant phenotype when placed on a high-fat diet and increased brown fat metabolism by elevated oxygen consumption, mitochondrial biogenesis, and uncoupling in BAT [16]. Recent studies have shown that overexpression of Twist1 is metabolically unfavourable as it indirectly contributes to fat accumulation, while the silencing of Twist1 enhances insulin sensitivity of adipocytes by antagonizing mitochondrial damage [21]. Moreover, in brown adipocytes, Twist1 interacts directly with Ppargc1a and serves as a key regulator of a negative feedback regulatory loop, orchestrating the balance between Ppargc1a induced transcription of target genes involved in uncoupling and Ppard isoform controlled brown fat metabolism resulting in a balanced energy homeostasis in response to energy substrate availability [16,22].…”
Section: Discussionmentioning
confidence: 99%
“…Cells with MiDAS appeared to have a SASP expression profile similar to siTWIST1-MSCs: they did not express IL-6 and IL8 and had an increased expression of IL-10 (Wiley et al, 2016). In addition, TWIST1 downregulation was demonstrated to promote mitochondrial dysfunction in lung cancer cells (Seo et al, 2014) and adipocytes (Lu et al, 2018).…”
Section: Twist1 Silencing Induces Cellular Senescence With a Specificmentioning
confidence: 99%